Growth, carbohydrate productivity and growth kinetic study of Halochlorella rubescens cultivated under CO2-rich conditions - Tan, Kean Meng; Mohd Asyraf Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study was parametrically established to investigate the effect of different initial pH cultivation medium from pH 4.00 to pH 10.00 and CO2 concentration from 0.04% to 25% (v/v) on the growth and carbohydrate content of Halochlorella rubescens. Changes in biochemical compositions were also analysed using Fourier-transform infrared spectroscopy (FTIR). The maximum concentration of biomass and the productivity carbohydrate were 0.49 ± 0.01 g/L and 22.42 ± 0.03 mg/L.d respectively, when pH 10.00 and 5% (v/v) CO2 concentration were used for cultivation. The FTIR analysis revealed obvious changes in the chemical functional groups for the1200-900 cm-1, 1655 cm-1 and 2850 cm-1 bands, which represent carbohydrate, protein and lipid in microalgal biomass under different cultivation conditions. At the completion of this study, two kinetic growth models, Logistic and Gompertz were evaluated for microalgae growth at elevated condition. The kinetic model analysis for Halochlorella rubescens growth at high CO2 condition fit well with the Gompertz equation with R2 value of 0.9977. The data acquired from this research was helpful for predicting the growth characteristics of microalgae in a CO2-rich medium and could act as an essential platform for the production of chemicals and biofuels.